Modelling Propagation of Technical Debt - Johannes Holvitie; Sherlock Licorish; Ville Leppänen (United States, 2022)
Noting the overwhelming speed during software development, and particularly in environments where rapid delivery is the norm, the lack of accumulated technical debt information could result in ineffective management. We introduce technical debt propagation channels in this paper to advance software maintenance research on two accounts: (1) We describe the fundamental components for the channels, allowing identification of distinct channels, and (2) we describe a procedure to identify and abstract technical debt channels in order to produce technical debt propagation models. Our propagation models pursue automation of technical debt information maintenance with program analysis results, and translation of the maintained information between existing-and currently disconnected-technical debt management solutions. We expect the immediate technical debt information to enhance applicability and effectiveness of existing technical debt management approaches.
2016 42th Euromicro Conference on Software Engineering and Advanced Applications (SEAA)